Off-pump coronary artery bypass (OPCAB) in complex coronary artery bypass procedures – a report of four cases and review of the literature - Harris, David G.; Janson, Jacques T. (SA Heart Journal, 2017)
Off-pump coronary artery bypass (OPCAB) surgery is a procedure that is still not widely used by all cardiac surgeons. In the USA about 20-25% of coronary artery bypass graft (CABG) surgery is done offpump. Current literature suggests that both OPCAB and CABG with cardiopulmonary bypass have similar mortality rates, but OPCAB surgery does offer less morbidity, and advantages in terms of mortality and stroke rates in certain high risk patients. We discuss the role of OPCAB surgery in high risk patients, especially redo operations through a left thoracotomy to protect an intact internal mammary artery (LIMA) graft to the left anterior descending artery (LAD) and in patients with a calcified ascending aorta. Four case reports are used as examples and the literature is reviewed, which shows a superior outcome with OPCAB surgery in these complicated cases.